KOMPARASI PENDAPATAN USAHATANI KARET RAKYAT MENGGUNAKAN BAHAN PEMBEKU DEORUB DAN NON DEORUB DI KECAMATAN LUBUK RAJA KABUPATEN OKU - Fatmayati, Anggi; Leni Sabrina (Jurnal Bakti Agribisnis, 2024)
Rubber plants are one of the important plantation commodities, both internationally and especially in Indonesia and have a very large role in the economic sector. Statistically there is a real (significant) difference between the average income of people's rubber farming using deorub and non-deorub freezing materials in Lubuk Raja District, OKU Regency. This can be seen from the calculated t value of 16.74 with a t table value of 2.058. Statistically there is a real (significant) difference between the average income of people's rubber farming using deorub and non-deorub freezing materials in Lubuk Raja District, OKU Regency. This can be seen from the calculated t value of 16.74 with the t table value of 2.058. Keywords: Rubber, Income, Comparative